2011
DOI: 10.1103/physrevd.84.064045
|View full text |Cite
|
Sign up to set email alerts
|

Naked singularity explosion in higher dimensions

Abstract: Motivated by the recent argument that in the TeV-scale gravity trans-Planckian domains of spacetime as effective naked singularities would be generated by high-energy particle (and black-hole) collisions, we investigate the quantum particle creation by nakedsingularity formation in general dimensions. Background spacetime is simply modeled by the self-similar Vaidya solution, describing the spherical collapse of a null dust fluid. In a generic case the emission power is found to be proportional to the quadrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…In the degenerate case, we have found that the power and energy diverge as the quartic and cubic inverse of the remaining time, respectively, and have shown that the power and energy depend on the total mass of dust fluid M phys despite the scale invariance of the central region. While a similar result has been obtained in the Vaidya case [19], it should be stressed that the behavior of the power and energy is different between the exactly degenerate case ζ = ζ c and the limit of ζ → ζ c .…”
Section: Conclusion and Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In the degenerate case, we have found that the power and energy diverge as the quartic and cubic inverse of the remaining time, respectively, and have shown that the power and energy depend on the total mass of dust fluid M phys despite the scale invariance of the central region. While a similar result has been obtained in the Vaidya case [19], it should be stressed that the behavior of the power and energy is different between the exactly degenerate case ζ = ζ c and the limit of ζ → ζ c .…”
Section: Conclusion and Discussionsupporting
confidence: 76%
“…(48). These features are similar to those in the higher-dimensional Vaidya (null dust) case [19]. Numerical values of (49) when the parameters are chosen as M P c 2 = 1 TeV and M phys c 2 = 5 TeV are given in Table 1.…”
Section: Degenerate Case (ζ = ζ C )supporting
confidence: 66%
See 2 more Smart Citations
“…Recently there has been significant activity in optical arbitrary waveform generation (OAWG) in which the amplitude and phase of individual lines of relatively high repetition rate frequency combs are controlled [1][2][3][4][5][6]. In the time domain, this leads to generation of wide temporal window (up to 100% duty factor) waveforms repeating at the repetition rate of the comb.…”
Section: Introductionmentioning
confidence: 99%